Combined application of superficial chemical peeling and facial oxygen therapy in the treatment of papulopustular rosacea - a case study - Pecarski, Danijela; Ignjatović, Milica; Filipović, Mila (Archives of Pharmacy, 2022)
Rosacea is a chronic, inflammatory skin disease that primarily affects the centrofacial region (cheeks, nose, chin, forehead) and eyes, characterized and diagnosed by recurrent flushing episodes, persistent erythema, inflammatory papules and/or pustules and telangiectasia. It cannot be cured, only "kept under control" by avoiding the causing factors, use of oral and/or topical drugs, appropriate cosmetic products and application of certain cosmetic treatments. Regarding the treatment of rosacea with pronounced inflammatory papules and pustules, the most common dermatological approach is the use of topical preparations with azelaic acid, while for the same indication in cosmetic procedures superficial azelaic chemical peeling is performed. The aim of this study was to evaluate the effectiveness of a new approach in the treatment of papulopustular rosacea - a combined application of superficial chemical peels with 20% azelaic acid and facial oxygen therapy. The client, 45 years old, female, diagnosed with papulopustular (PP) rosacea, diffuse erythema and PP lesions on the cheeks, forehead and chin, without pharmacological therapy, underwent superficial chemical peel treatment with 20% azelaic acid. The solution was applied to the PP lesions region, neutralized and hydraporation was performed with oxygen jet and hyaluronic acid serum, for 10 minutes. Seven days after the treatment, there were a reduction of inflammatory papules and pustules of the centrofacial region, reduction of erythema and improvement of the skin appearance. Skin condition, with adequate skin care advice, remained unchanged even after three months. Mentioned approach could be successfully in the treatment of mild to moderate papulopustular rosacea.